(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This paper aims to describe an effective strategy for improving students’ speaking skills at the junior high school level using the ESA (Engage, Study, Activate) method. The data in this study were obtained through pre-test and post-test. The results showed an increase in the post-test. In the pre-test the average student score was 52.78, while in the post-test there was an increase to 80.28. Based on the Paired Sample T Test, a significance value (2 tailed) was obtained of 0.001 <0.05 indicating a significant difference between the initial and final variables. This shows that using the ESA method can improve students’ speaking skills. The ESA method is an effective approach in improving junior high school students’ speaking skills.